Therapeutic Targeting of Cancer Stem Cells - Maugeri-Saccà, Marcello; Zeuner, Ann; De Maria, Ruggero (Frontiers in Oncology, 2011)
Recent breakthroughs in translational oncology are opening new perspectives for the treatment of cancer. The advent of targeted therapies has provided the proof-of-concept to selectively turn-off deregulated oncogenic proteins, while the identification and validation of predictive biomarkers of response has allowed to improve, at least in some cases, their performance. Moreover, a subpopulation of tumor-propagating cells has been identified from many solid and hematological tumors. These cells share functional properties of normal stem cells, and are commonly referred to as cancer stem cells (CSCs). It is emerging that CSCs are defended against broadly-used anticancer agents by means of different, partly interconnected, mechanisms. However, CSCs rely on specific pathways involved in self-renewal that can be pharmacologically antagonized by experimental molecular targeted agents, some of which have recently entered early phases of clinical development. Here, we discuss the spectrum of pharmacological strategies under clinical or preclinical development for CSCs targeting.